A conceptual model for autonomic relationships in the Social Internet of Things - Camargo, Leandro; Pernas, Ana Marilza; Yamin, Adenauer (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia), 2022)
Miniaturization of computing devices allows everyday physical objects to communicate on a network through various ubiquitous media. In this scenario, smart things can socially interact autonomously with each other. In order to make this scenario a reality, this work presents the conception of a Conceptual Model for the dynamic management of the relationships established between intelligent objects, thus contributing to the consolidation of the Social Internet of Things. We designed a friendship recommendation and social circle composition approach that monitors interaction and highlights the most relevant objects for fulfilling requests. Additional contributions are: (i) simplification of the interaction process between objects; (ii) timely indication of friendship; and (iii) a structuring proposal for the social circle. The Link Analysis technique is the basis of the model implemented to identify connections between individuals and qualify interactions. In addition, the composition of the social circle is guided by the theory of social networks of the Organizational Network Analysis methodology, aiming to simplify indications of new friendships. Results of partial evaluations demonstrated the potential of the implemented model to correctly classify the interactions and roles of objects defined in the relationships. This validation leads to planned future work and the improvement of the implemented model.